A Radiant Light: an Introduction to Matthew Arnold: Insights into Matthew Arnold's worldview in the Victorian era (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Arnold was as he saidhimself, “a liberal of the Future” – a future which has not yet arrived.  He lived through a period of radical change –the Victorian age, and spoke more wisely of continuing problems than ourfashionable prophets of moral and social revolution or their reactionaryopponents.